2016
DOI: 10.4236/mrc.2016.51001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alkali Carbonate/Bicarbonate on Citral Hydrogenation over Pd/Carbon Molecular Sieves Catalysts in Aqueous Media

Abstract: The efficient citral hydrogenation was achieved in aqueous media using Pd/CMS and alkali additives like K 2 CO 3 . The alkali concentrations, reaction temperature and the Pd metal content were optimized to enhance the citral hydrogenation under aqueous media. In the absence of alkali, citral hydrogenation was low and addition of alkali promoted to ~92% hydrogenation without reduction in the selectivity to citronellal. The alkali addition appears to be altered the palladium sites. The pore size distribution rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…24 Undoubtedly the modification of the physico-chemical interactions between the particle surface and the ions nearby may improve the adsorption of the conjugated olefinic bond over the isolated one and thus increase the selectivity to citronellal over dihydrocitronellal. [25][26] This effect has already been observed in other studies by Krishna et al 23,27 The colloidal stability was also confirmed by the Turbiscan stability study of Pd@CTACl suspension (with or without KOH), over 7 days (Figure 5). In both cases, TSI values inferior to 0.15 were obtained, thus ranking the suspensions in the green A+ color on the TSI scale, which is the best stability mark.…”
Section: Entrysupporting
confidence: 78%
“…24 Undoubtedly the modification of the physico-chemical interactions between the particle surface and the ions nearby may improve the adsorption of the conjugated olefinic bond over the isolated one and thus increase the selectivity to citronellal over dihydrocitronellal. [25][26] This effect has already been observed in other studies by Krishna et al 23,27 The colloidal stability was also confirmed by the Turbiscan stability study of Pd@CTACl suspension (with or without KOH), over 7 days (Figure 5). In both cases, TSI values inferior to 0.15 were obtained, thus ranking the suspensions in the green A+ color on the TSI scale, which is the best stability mark.…”
Section: Entrysupporting
confidence: 78%
“…. Consequently, the modification of the surface properties and adsorption/desorption phenomena upon the addition of a base may improve the hydrogenation of the conjugated olefinic bond and thus increase the selectivity to citronellal over dihydrocitronellal. , This effect has already been observed in other studies and could be explained by an electrostatic effect of potassium cations near Pd active sites, as well as the increased solubility of the substrate upon the addition of alkali. ,, The colloidal stability was also confirmed by the Turbiscan stability study of Pd@CTACl suspension (with or without KOH), over 7 days (Figure ). In both cases, Turbiscan stability index (TSI) values inferior to 0.15 were obtained, thus ranking the suspensions in the green A+ color on the TSI scale, which is the best stability mark.…”
Section: Resultssupporting
confidence: 55%
“…31,33 This effect has already been observed in other studies and could be explained by an electrostatic effect of potassium cations near Pd active sites, as well as the increased solubility of the substrate upon the addition of alkali. 28,34,35 The colloidal stability was also confirmed by the Turbiscan stability study of Pd@CTACl suspension (with or without KOH), over 7 days (Figure 4). In both cases, Turbiscan stability index (TSI) values inferior to 0.15 were obtained, thus ranking the suspensions in the green A+ color on the TSI scale, which is the best stability mark.…”
Section: ■ Results and Discussionmentioning
confidence: 68%
“…Firstly, tungsten oxides are generally inactive toward alkaline HER, not to mention that in the present case, the amount of WO x is very small. As for the Mo 2 N, although there have been reports on its activity as a HER electrocatalyst, it is not as dominating as QAMN. In fact, we measured the linear sweep voltammetry (LSV) curves of the as‐prepared catalysts.…”
Section: Resultsmentioning
confidence: 96%